Vitamin D and Delirium in Older Adults: A Case-Control Study in Geriatric Acute Care Unit - Chouët, Justine; Sacco, Guillaume; Karras, Spyridon N.; Llewellyn, David J.; Sánchez-Rodríguez, Dolores; Annweiler, Cédric (Frontiers in Neurology, 2020)
Objective. Vitamin D is involved in brain health and function. Our objective was to determine whether the serum 25-hydroxyvitamin D (25OHD) concentration was associated with delirium in a case-control study of geriatric inpatients. Methods. Sixty cases with delirium (mean±SD, 84.8±5.7years; 58.3% female) and 180 age- and gender-matched controls were enrolled in a geriatric acute care unit between 2012 and 2014. The diagnosis of delirium was made using the Confusion Assessment Method. Hypovitaminosis D was defined using consecutively the consensual threshold value of 50nmol/L and a threshold value calculated from a sensitivity-specificity analysis. Age, gender, number of acute diseases, use of psychoactive drugs, season of testing, and serum concentrations of calcium, parathyroid hormone, creatinine, albumin, TSH, vitamin B9 and vitamin B12 were used as potential confounders. Results. The 60 cases with delirium exhibited lower 25OHD concentration than 180 matched controls (35.4±30.0nmol/L versus 45.9±34.5nmol/L, p=0.035). Increased 25OHD concentration was associated with a decrease in delirium prevalence (OR=0.99 [95CI: 0.98-0.99] per nmol/L of 25OHD, p=0.038). The concentration distinguishing between cases and controls with the best sensitivity-specificity was found between 29.5 and 30.5 nmol/L. The regression models showed that delirium was associated with hypovitaminosis D defined either as 25OHD≤50nmol/L (OR=2.37 [95CI: 1.07-5.25], p=0.034) or as 25OHD≤30nmol/L (OR=2.66 [95 CI: 1.30-5.45], p=0.008). Conclusions. Decreased serum 25OHD concentrations were associated with delirium among acute geriatric inpatients. The threshold concentration to differentiate between cases and controls was around 30nmol/L.